2014
DOI: 10.1111/1442-1984.12057
|View full text |Cite
|
Sign up to set email alerts
|

Does successful ovule development depend on its position within the pod? Examples from Neotropical Fabaceae

Abstract: Previous studies have shown a nonrandom pattern of ovule fate probabilities according to ovule position in legume pods. Here, we tested how ovule position within the pods of two Fabaceae affects its fate. We expected higher proportion of well‐formed seeds near the fruit tips and of unfertilized and aborted ovules near fruit bases. We collected pods of Poincianella pyramidalis and Anandenanthera colubrina in a seasonal dry forest in northeastern Brazil and recorded total pod length and ovule number, position, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The linear arrangement of ovules within the pods of legumes provides a way to assess the effect of the maternal environment on ovule and seed fates (Silveira and Fuzessy, 2015). We found a strong nonrandom pattern of ovule‐fate probabilities, depending on ovule position in the pods of V. unijuga .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear arrangement of ovules within the pods of legumes provides a way to assess the effect of the maternal environment on ovule and seed fates (Silveira and Fuzessy, 2015). We found a strong nonrandom pattern of ovule‐fate probabilities, depending on ovule position in the pods of V. unijuga .…”
Section: Discussionmentioning
confidence: 99%
“…We found a strong nonrandom pattern of ovule‐fate probabilities, depending on ovule position in the pods of V. unijuga . Pollen limitation, which is inferred from a high proportion of nonfertilized ovules at the base of the pod (Silveira et al, 2015), accounted for a higher proportion of ovule loss in V. unijuga compared with resource limitation, which is inferred from aborted fertilized ovules and low conversion of ovules into seeds near the base of the pod (Silveira and Fuzessy, 2015). The low likelihood of ovules being fertilized at the base of V. unijuga pods suggested that pollen quality and/or quantity are strongly limited by the harsh subalpine environments.…”
Section: Discussionmentioning
confidence: 99%